Application of Carbon Nanomaterials in Human Virus Detection (2020)
Human-pathogenic viruses are still a chief reason for illness and death on the globe, as epitomized by the COVID-19 pandemic instigated by a coronavirus in 2020. Multiple novel sensors have been invented because diseases must be detected and diagnosed as early as possible, and recognition methods have to be carried out with minimal invasivity. Sensors have been particularly developed focusing on miniaturization by the use of nanomaterials for fabricating nanosensors. The nano-sized nature of nanomaterials and their exclusive optical, electronical, magnetical, and mechanical attributes can enhance patient care through the use of sensors with minimal invasivity and extreme sensitivity. Amongst the nanomaterials utilized for fabricating nano-sensors, carbon-based nanomaterials are promising as these sensors respond better to signals in various sensing settings. This review provides an overview of the recent developments in carbon nanomaterial-based biosensors for viral recognition based on the biomarkers that arise from the infection, the nucleic acids from the viruses, and the entire virus. The role of carbon nanomaterials is highlighted by the improvement of sensor and recognition functionality. The Dengue virus, Ebola virus, Hepatits virus, human immunodeficiency virus (HIV), influenza virus, Zika virus and Adenovirus are the virus types reviewed to illustrate the implementation of the techniques. Finally, the drawbacks and advantages of carbon nanomaterial-based biosensors for viral recognition are identified and discussed.